Insights into immune-related adverse events in colorectal cancer patients receiving neoadjuvant immunotherapy: findings from a multicenter registry study - Wang, Chentong; Wang, Quan; Zhou, Jiaolin; Zhou, Aiping; Wu, Xiaojian; Yu, Guanyu; Zhou, Lei; Zhu, Yuping; Chen, Weijie; Qiu, Xiaoyuan; Sun, Liting; Gong, Yang; et al. (Frontiers in Immunology, 2025)
BackgroundThe growing use of immune checkpoint inhibitors (ICIs) in the neoadjuvant treatment of colorectal cancer (CRC) has highlighted immune-related adverse events (irAEs) as a major concern. This study aimed to investigate the characteristics of irAEs.MethodsThis study was a retrospective, multicenter, registry-based investigation conducted in China, including 148 patients who developed irAEs after neoadjuvant immunotherapy between September 2020 and March 2024. The study analyzed the types, severity, risk factors and management strategies of irAEs. Data were collected on patient demographics, tumor assessments, neoadjuvant therapy regimens, and irAEs. Statistical analyses were conducted to identify the characteristics of irAEs and to assess their impact on surgical outcomes.ResultsAmong the 148 patients, a total of 203 irAEs were documented, primarily affecting the skin, endocrine system, and liver. Most irAEs (95.6%) were mild-to-moderate in severity and were effectively managed with symptomatic treatment. Hepatotoxicity was the most frequent irAE, notably associated with the combination of radiotherapy and the CAPOX chemotherapy regimen. The severity of irAEs did not affect surgical complexity or postoperative complications.ConclusionNeoadjuvant immunotherapy combined with chemoradiotherapy demonstrates a favorable safety profile, with most irAEs being manageable. The findings support the clinical feasibility of combined regimens in CRC treatment, emphasizing the need for individualized management and extended follow-up for late-onset or chronic irAEs.